Pengaruh Struktur Dan Proses Corporate Governance Terhadap Kinerja Perusahaan Di Indonesia - Tri Cahyo Nugroho; Warseno Warseno; Isrial Isrial (UNIVERSITAS RAHARJA, 2020)
The aims of the research is analyzing the influence of corporate governance structure and process on firm performance in Indonesia . The Indicators in this research is : institutional ownership, independent commissioner, board of directors size, board of directors meeting, board of commissioners meeting and audit committee meeting. Firm performance measured by TobinsQ value. This research uses multiplier regression analysis as statistic instrument. Population in this research is consumer goods manufacture listed on Bursa Efek Indonesia 2001-2015 obtain 85 samples base on determined criteria. The results of this research show that institutional ownership, independent commissioner and board of commissioners meeting has significant positive influence on firm performance, board of directors size and board of director meeting has significant negative influence on firm performance, while the audit committee meeting has no influence on firm performance